2020
DOI: 10.1111/sms.13742
|View full text |Cite
|
Sign up to set email alerts
|

Cycling‐specific isometric resistance training improves peak power output in elite sprint cyclists

Abstract: Introduction This study aimed to assess the efficacy of a 6‐week cycling‐specific, isometric resistance training program on peak power output (PPO) in elite cyclists. Methods Twenty‐four elite track sprint cyclists were allocated to EXP (n = 13, PPO, 1537 ± 307 W) and CON (n = 11, PPO, 1541 ± 389 W) groups. All participants completed a 6‐week training program; training content was identical except participants in the EXP group replaced their usual compound lower body resistance training exercise with a cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…via varied prescription or the introduction of novel methods) in training stimuli to achieve further increases in maximal power [112,118,121,122]. For example, novel strategies such as velocity-based training [123,124], eccentric training [125][126][127][128], isometric training [74] and electromyostimulation [129,130] incorporated alongside traditional strength training may be effective in inducing further increases in maximal and high-velocity force production (e.g. via enhanced neural adaptations, preferential fast twitch fibre hypertrophy and increased muscle-tendon unit stiffness) in strength trained individuals.…”
Section: Developing Maximal Cycling Powermentioning
confidence: 99%
See 2 more Smart Citations
“…via varied prescription or the introduction of novel methods) in training stimuli to achieve further increases in maximal power [112,118,121,122]. For example, novel strategies such as velocity-based training [123,124], eccentric training [125][126][127][128], isometric training [74] and electromyostimulation [129,130] incorporated alongside traditional strength training may be effective in inducing further increases in maximal and high-velocity force production (e.g. via enhanced neural adaptations, preferential fast twitch fibre hypertrophy and increased muscle-tendon unit stiffness) in strength trained individuals.…”
Section: Developing Maximal Cycling Powermentioning
confidence: 99%
“…An evenly mixed distribution of fast and slow twitch fibres across agonist musculature has been proposed to produce an optimal cadence of around 120 rpm in healthy non-power trained adults [ 30 , 31 , 45 , 72 ]. Power trained athletes and individuals genetically endowed with a high proportion of fast twitch fibres may exhibit optimal cadences of 130 rpm and above [ 72 74 ].
Fig.
…”
Section: Maximal Cycling Powermentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a custom-built isometric dynamometer and the specific protocol used to measure MVT, RTD and VA during knee extension is detailed elsewhere. 21 Briefly, the riders were positioned in a custom-built dynamometer with hip and knee joint angles at 125 o and 115 o , respectively. A calibrated S-beam strain gauge (Force Logic, Swallowfield, UK) attached securely to the lower leg (~15% of tibial length above the medial malleolus) was used to measure knee extension force.…”
Section: Isometric Dynamometrymentioning
confidence: 99%
“…MVT could be a target of training programmes aimed at increasing W, and indeed sprint cyclists commonly commit large portions of their training programmes to resistance exercise. There is evidence that increasing (lower extremity) muscle strength is effective at increasing PPO, in elite cyclists, 21 and resistance exercise has emerged as the only efficacious training methodology that might evoke an increase in the W 15 and severe-intensity exercise performance without affecting CP. 15,16 Previous work 26 in an elite population suggested that muscle volume and architecture are potentially important determinants of PPO in elite athletes.…”
Section: Relationship Of Neuromuscular Measures and Wmentioning
confidence: 99%